A preliminary investigation on the effects of the different concentrations of sodium cyanide on Epinephelus coiodes - Salazar, Aileen Valle
Fish samples exposed to 1 ppm dilution get a mean of 0.0797 part per million cyanide concentration while a mean of 0.0718 ppm CN concentration for the fish samples in the 5 ppm dilution and a zero concentration for the 0.05 ppm exposed fish samples.